Wyjście z kryzysu – proces stabilizacji oraz odbudowa państwa afgańskiego - Weosłowska-Maciejewska, Anna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Afghanistan is one of the most unstable countries in the world. The process of reconstruction began in 2001 when Taliban regime was defeated. It is difficult to stabilize situation in Afghanistan. Stabilization requires the help from an international community, especially the European Union, the ISAF and the United States of America. The support is mostly financial and material. However, there are many problems such as production and smuggling of drugs. Another problem is also Afghans’ huge poverty. These factors influence the completion of tasks negatively.